10 Jahre Artothek Berlin. - Neuer Berliner Kunstverein, Berlin (Berlin : Neuer Berliner Kunstverein, 1980)
Aarso, Carl-Henning ; Abrahams, Ivor ; Ackermann, Peter ; Akrithakis, Alexis ; Albert, Hermann ; Altenbourg, Gerhard ; von Altrock, Hartmut ; Andrées, Gerhard ; Anlauf, Günter ; Antes, Horst ; Arlt, Dietrich ; Arnim, Bettina v. ; Arntz, Gerd ; Arroyo, Eduardo ; Asmus, Dieter ; Attersee, Ch.-L. ; Axmann, Elisabeth ; Bader, Alexander ; Badur, Frank ; Baehr, Ulrich ; Ballin, Iris ; Barahona, Mario ; Barge, Michael Jens ; Bargheer, Eduard ; etc.
10 Jahre Artothek Berlin, Neuer Berliner Kunstverein, Berlin, 1980
boek